(untitled) (Research, Society and Development, 2022)
Pernambuco is known for the beauty of its beaches with high temperatures, which are frequented for leisure activities. In this way, the beaches have become an environment of great circulation, in addition to the expansion of industries, agriculture, livestock and urban centers, contributing to the impact of ecosystems. The set of these factors directly influence the rise in the rate of contamination of saline water, due to the disposal of inorganic waste at sea. Thus, the present study aimed to evaluate the physical-chemical and microbiological parameters of sea Pernambuco. The collections were carried out from April to May 2022 ar Candeias beaches (P1 and P2) and paiva beach and were subjected to physicochemical and microbiological analysis. The parameters of acidity, alkalinity, chlorides, sulfates, calcium, magnesium, total hardness, sodium, potassium, the series of solids, DQO, DBO, despite not being controlled by CONAMA ordinance 357/2005 for class 1,2 and 3 saline waters, have high values, mainly at points (P1 and P2), indicating the presence of effluent discharges on the coast. The microbiological analyzes shows the presence of total and fecal coliforms, where the existence of the bacteria Escherichia coli variety I, Enterobacter aerogenes variety I and Enterobacter aerogenes variety II were identified. However, microbiological analyzes showed the existence of a high level of contamination on the beaches of the Pernambuco coast, making it necessary to monitor the saline waters to guarantee their sanitary quality for use.